2020
DOI: 10.1111/1749-4877.12434
|View full text |Cite
|
Sign up to set email alerts
|

Resting metabolic rates increase with elevation in a mountain‐dwelling lizard

Abstract: Individuals that inhabit broad elevational ranges may experience unique environmental challenges. Because temperature decreases with increased elevation, the ectotherms living at high elevations have to manage limited activity time and high thermoregulatory effort. The resting metabolic rate (RMR) of a postabsorptive animal is related to its total energy requirements as well as many other fitness traits. Mesquite lizards (Sceloporus grammicus) living on La Malinche Volcano, Mexico, inhabit a wide elevational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 109 publications
(128 reference statements)
2
18
1
Order By: Relevance
“…It has generally been found that ectotherms (fish and especially insects) from cold climates have elevated metabolic rates -the metabolic cold adaptation hypothesis (Addo-Bediako et al, 2002;Gaston et al, 2009;Holeton, 1974;White et al, 2012;Wohlschlag, 1960). This pattern has also been reported in lizards (Al-Sadoon, 1986;Angilletta, 2001;Christian et al, 1998;Hare et al, 2010;Patterson & Davies, 1989;Plasman et al, 2020) and our data indicate it is a widespread phenomenon (see also Žagar et al, 2018). The correlation with maximum temperatures rather than minimum temperatures is consistent with the original idea of metabolic cold adaptation whereby the overall physiological processes are adjusted upwards as species invade colder environments (Kawall et al, 2002).…”
Section: Thermal Physiologysupporting
confidence: 83%
“…It has generally been found that ectotherms (fish and especially insects) from cold climates have elevated metabolic rates -the metabolic cold adaptation hypothesis (Addo-Bediako et al, 2002;Gaston et al, 2009;Holeton, 1974;White et al, 2012;Wohlschlag, 1960). This pattern has also been reported in lizards (Al-Sadoon, 1986;Angilletta, 2001;Christian et al, 1998;Hare et al, 2010;Patterson & Davies, 1989;Plasman et al, 2020) and our data indicate it is a widespread phenomenon (see also Žagar et al, 2018). The correlation with maximum temperatures rather than minimum temperatures is consistent with the original idea of metabolic cold adaptation whereby the overall physiological processes are adjusted upwards as species invade colder environments (Kawall et al, 2002).…”
Section: Thermal Physiologysupporting
confidence: 83%
“…While we found no difference between the metabolic rates of geckos across slopes, Plasman et al (2020) found that high altitude Sceloporus grammicus lizards had higher metabolic rates than low altitude individuals at all measured temperatures (ranging between 15°C and 35°C). The study sites investigated by Plasman et al (2020) were located 5-11 km apart, and mean annual temperatures differed by ~5°C between sites and by ~10°C between the highest and lowest sites. This is a much larger contrast than the 2°C difference in annual air temperature between slopes in Nahal Oren.…”
Section: Discussioncontrasting
confidence: 86%
“…When compared to warm environments, ectotherms from cold environments tend to have higher metabolic rates (White et al, 2012;Žagar et al, 2018). This is known as the metabolic cold adaptation hypothesis (Gaston et al, 2009), and it has been reported for lizards (Angilletta, 2001;Hare et al, 2010;Plasman et al, 2020;but see Tsuji, 1988).…”
Section: Discussionmentioning
confidence: 89%